2013
DOI: 10.1152/jn.00708.2012
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic modulation of norepinephrine release and uptake in rat brain cortex: contribution of glial cells

Abstract: Pinho D, Quintas C, Sardo F, Cardoso TM, Queiroz G. Purinergic modulation of norepinephrine release and uptake in rat brain cortex: contribution of glial cells. J Neurophysiol 110: 2580 -2591, 2013. First published September 11, 2013 doi:10.1152/jn.00708.2012.-The pathogenesis of psychiatric and neurodegenerative diseases is often associated with a deregulation of noradrenergic transmission. Considering the potential involvement of purinergic signaling in the modulation of noradrenergic transmission in the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 78 publications
0
9
1
Order By: Relevance
“…It is reported that P2Y6 was mainly expressed in microglia and astrocytes 31–33 . To confirm the distribution of P2Y6 in ACC, different cell markers were used for immunofluorescence study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that P2Y6 was mainly expressed in microglia and astrocytes 31–33 . To confirm the distribution of P2Y6 in ACC, different cell markers were used for immunofluorescence study.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that P2Y6 was mainly expressed in microglia and astrocytes. [31][32][33] To confirm the distribution of P2Y6 in ACC, different cell markers were used for immunofluorescence study. Surprisingly, P2Y6 was predominately co-localized with NeuN, but only a few with Iba1 and GFAP (Figure 5A).…”
Section: P2y6 Was Mainly Expressed In Acc Neuronsmentioning
confidence: 99%
“…Cells were allowed to attach for 24 hr and then were treated with ADA (0.3 U/mL ) or increasing concentrations of nucleosides (ADO or INO) for different time points (1–48 hr), depending on the experiment performed. When antagonists (MRE 3008F20 (selective A 3 AR, 10 nM ); CGS 15943 (non‐selective AR, 100 nM ); MRS 2500 (selective P2Y 1 R, 1 μM )) were used, these compounds were added 30 min. prior to the addition of other compounds.…”
Section: Methodsmentioning
confidence: 99%
“…P2Y6 is expressed in microglia, but not in astrocytes [ 152 , 153 ], although there is a pharmacological report suggesting the presence of P2Y6 in cultured astrocytes [ 154 , 155 ], and some reports locate P2Y6 in subsets of neurons, mainly in the periphery [ 156 , 157 ]. Interestingly, the expression P2Y6 in microglia is sensitive to neuronal excitability [ 158 ].…”
Section: P2y6/12 Receptorsmentioning
confidence: 99%